2018
DOI: 10.1037/tra0000333
|View full text |Cite
|
Sign up to set email alerts
|

Italian validation of the Childhood Trauma Questionnaire—Short Form on a college group.

Abstract: Findings highlighted reliability, structure, and concurrent validity for the Italian CTQ-SF and thus supported the implementation of the Italian version of the Childhood Trauma Questionnaire-Short Form in the assessment of traumatic experiences and the screening in nonclinical groups. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Previous research has demonstrated that the CTQ-SF has good reliability and validity (Bernstein et al, 2003; Hernandez et al, 2012; Thombs, Bernstein, Lobbestael, & Arntz, 2009). In the current study, we administered the Italian CTQ-SF (Sacchi, Vieno, Simonelli, 2017), in which the original five-factor structure is confirmed and the Cronbach’s alpha ranges across subscales between .87 and .96.…”
Section: Methodsmentioning
confidence: 95%
“…Previous research has demonstrated that the CTQ-SF has good reliability and validity (Bernstein et al, 2003; Hernandez et al, 2012; Thombs, Bernstein, Lobbestael, & Arntz, 2009). In the current study, we administered the Italian CTQ-SF (Sacchi, Vieno, Simonelli, 2017), in which the original five-factor structure is confirmed and the Cronbach’s alpha ranges across subscales between .87 and .96.…”
Section: Methodsmentioning
confidence: 95%
“…The adverse childhood experiences were measured through five subscales from the Italian version of the Childhood Trauma Questionnaire -Short Form (CTQ-SF; Bernstein et al, 2003;Petrone et al, 2012;Sacchi et al, 2018), which is one of the most used retrospective instruments for detecting adverse experiences in the family of origin during childhood or adolescence, as well as through six ad hoc items assessing violence witnessed in the family during the same period. The CTQ-SF subscales measure: physical abuse (five items; e.g., "People in my family beat me so hard they left bruises or marks on me"), emotional abuse (five items; e.g., "People in my family used to offend and insult me"), sexual abuse (five items; e.g., "Someone tried to get me to do sexual things or watch sexual things"), physical neglect (five items; e.g., "I didn't have enough to eat"), and emotional neglect (five items; e.g., "People in my family felt very close"reverse item).…”
Section: Measures Acesmentioning
confidence: 99%
“…Yet, results from studies on the five-factor structure reported in the original manual (Bernstein & Fink, 1998) have been mixed, with some studies supporting it whilst others only obtain partial support or suggest alternative models. A number of studies, based on both clinical and non-clinical samples, and including both adolescents and adults, predominantly from North America and Europe, have obtained support for the five-factor structure reported in the CTQ-SF manual (Bernstein et al, 2003;Dovran et al, 2013;Dudeck et al, 2015;Hernandez et al, 2013;Sacchi, Vieno, & Simonelli, 2018;Thombs, Bernstein, Lobbestael, & Arntz, 2009;Thombs, Lewis, Bernstein, Medrano, & Hatch, 2007). Moreover, some of these studies also tested and demonstrated the structural invariance or measurement equivalence of the original CTQ-SF five-factor structure across gender, age and subsamples (Bernstein et al, 2003;Dovran et al, 2013;Thombs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This alternative CTQ-SF five-factor was found to be the most appropriate when compared to the original factor solution in a mixed Brazilian sample when the total CTQ-SF score was also included at the second order level (Grassi-Oliveira et al, 2014). Another study, based on an Italian college sample, though finding that the five-factor structure specified in the CTQ-SF manual provided best fit, also found that a fourfactor first order structure (wherein items from the Physical and Emotional neglect scales were collapsed into one single Neglect scale) provided a good fit (Sacchi et al, 2018). Given these indecisive research findings, more research examining the factorial structure in clinical samples is important and needed.…”
Section: Introductionmentioning
confidence: 99%